Effects of fertilizer placements and irrigation frequencies on growth, mineral nutrition and yield of tomatoes grown in soilless culture - Ismail, Mohd Razi; H., Hasni (International Society for Horticultural Science, 1993)
The experiment was conducted to investigate the response of different fertilizer placements and irrigation frequencies on growth, mineral nutrition, and yield of tomatoes grown in soilless culture. Four different fertilizer formulations were applied to the plants viz. Cooper Formulation, Amina (Organic Fertilizer), Osmocote (slow release fertilizer) and Nitrophoska Blue at two different frequencies of irrigation i.e once and twice daily. Mineral nutrient analyse showed a higher uptake of N, P, K, Ca, Mg in the leaves from plants grown with Cooper Formulation. The deficiency in Ca was clearly evident on young leaves of plants grown with the slow release fertilizer. Yield was highest when plants were grown with Cooper Formulation. There was no significant difference between irrigation frequencies on the growth and mineral nutrient uptake. Yield increased when plants were irrigated twice daily but total soluble solids of fruits was reduced.